2021
DOI: 10.4103/psychiatry.indianjpsychiatry_448_20
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of retention in the treatment for opioid dependence

Abstract: Background: Literature on a longitudinal study of the determinants of treatment retention for patients with opioid dependence is limited. Aim: To find out patient- and treatment-related (buprenorphine-naloxone-assisted treatment [BNX treatment] versus naltrexone treatment) predictors for retention in maintenance treatment. Materials and Methods: A total of 100 participants with opioid dependence were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, no significant disparities were observed in age at first use or route of intake between the two groups. In a study by Shouan et al, no significant difference was observed in any of the demographic and clinical profiles of the groups that followed up and those who dropped out except for the route of drug use; non-intravenous drug use was associated with dropping out [30].…”
Section: Discussionmentioning
confidence: 91%
“…However, no significant disparities were observed in age at first use or route of intake between the two groups. In a study by Shouan et al, no significant difference was observed in any of the demographic and clinical profiles of the groups that followed up and those who dropped out except for the route of drug use; non-intravenous drug use was associated with dropping out [30].…”
Section: Discussionmentioning
confidence: 91%
“…Empirical studies of OST effectiveness and integration: We reviewed the empirical evidence on effectiveness of OST for various outcomes in PWIDs. Most of the studies were conducted with treatment-seeking populations with convenience sampling and showed better treatment retention rates, improved physical and mental health and decreased needle sharing and crime 81 82 83 84 85 . summarizes these findings.…”
Section: Resultsmentioning
confidence: 99%